Mutagenesis of GPR139 reveals ways to create gain or loss of function receptors. Issue 1 (7th February 2019) - Wang, Lien; Lee, Grace; Shih, Amy; Kuei, Chester; Nepomuceno, Diane; Wennerholm, Michelle; Fan, Frances; Wu, Jiejun; Bonaventure, Pascal; Lovenberg, Timothy W.; Liu, Changlu
Abstract: GPR139 is a Gq‐coupled receptor activated by the essential amino acids L‐tryptophan (L‐Trp) and L‐phenylalanine (L‐Phe). We carried out mutagenesis studies of the human GPR139 receptor to identify the critical structural motifs required for GPR139 activation. We applied site‐directed and high throughput random mutagenesis approaches using a double addition normalization strategy to identify novel GPR139 sequences coding receptors that have altered sensitivity to endogenous ligands. This approach resulted in GPR139 clones with gain‐of‐function, reduction‐of‐function or loss‐of‐function mutations. The agonist pharmacology of these mutant receptors was characterized and compared to wild‐type receptor using calcium mobilization, radioligand binding, and protein expression assays. The structure‐activity data were incorporated into a homology model which highlights that many of the gain‐of‐function mutations are either in or immediately adjacent to the purported orthosteric ligand binding site, whereas the loss‐of‐function mutations were largely in the intracellular G‐protein binding area or were disrupters of the helix integrity. There were also some reduction‐of‐function mutations in the orthosteric ligand binding site. These findings may not only facilitate the rational design of novel agonists and antagonists of GPR139, but also may guide the design of transgenic animal models to study the physiological function of GPR139.